Spatial and Interannual Variability in Distributions and Cycling of Summer Biogenic Sulfur in the Bering Sea. Issue 9 (8th May 2019) - Li, Cheng‐Xuan; Wang, Bao‐Dong; Wang, Zi‐Cheng; Li, Jiang; Yang, Gui‐Peng; Chen, Jian‐Fang; Lin, Li‐Na; Lyu, Yang; Guo, Fu
Abstract: In the Bering Sea, summer dimethylsulfide (DMS) and dimethylsulfoniopropionate (DMSPd and DMSPp) exhibited substantial spatial and interannual variations during 2012–2016, encompassing both cold (2012) and warm (2014 and 2016) temperature regimes. Summer average chlorophyll a, DMS, and DMSPd concentrations in the upper water increased significantly, paralleling a 1.6 °C increase in seawater temperature. High DMS/DMSPp regions in the upper 50 m at 177°E–175°W extended both north‐eastward and south‐westward, which were associated with elevated phytoplankton biomass and concurrent proportion of dinoflagellates in phytoplankton community in warm years. Simultaneously, these patches spread vertically throughout the upper 200 m in warm years, which corresponded with rapid bacteria consumption and abundant small copepods at the 50–200‐m layer in 2014 and 2016. Starting from 4.88 μmol/(m 2 day), summer average DMS fluxes increased sharply by threefold to fivefold in response to a warming of 2.8 °C in the surface water during 2012–2016. Plain Language Summary: The Bering Sea has undergone a warming and responds rapidly to climate change on temporal scales. The resulting marine ecosystem reorganization in the Bering Sea has the potential to exert profound impacts on the local marine biogeochemical cycles and the sea‐to‐air fluxes of dimethylsulfide (DMS). Data on temporally detailed DMS and DMSP measurements in the Bering Sea are rare. Three summer cruises to the Bering Sea, one covering the cold year (2012) and two covering warm years (2014 and 2016), provided an opportunity to study how oceanic biogenic dimethylated sulfur compounds may respond to spatiotemporal variations to ocean warming resulting from climate change. Seawater warming of 1.6 °C in the upper layer of the basin‐slope‐shelf section from cold to warm years was accompanied by elevated phytoplankton biomass, further leading to increases in DMS and DMSPd concentrations. Both vertical and horizontal extensions of high DMS/DMSPp patches at 177°E–175°W from 2012 to 2016 were caused by variations in plankton biomass and community structure. Summer DMS sea‐to‐air fluxes increased sharply by threefold to fivefold due to a coincident warming of 2.8 °C in the surface water, which would exert climate cooling effects inverse to those of the CO2 built up in the Bering Sea. Key Points: Interannual ascending trends in Chl a, DMS, and DMSPd concentrations corresponded with seawater warming of 1.6 °C in the upper water Both vertical and horizontal extensions of high DMS/DMSPp patches were caused by variations in plankton biomass and community structure Summer DMS fluxes increased sharply by threefold to fivefold due to a warming of 2.8 °C in the surface water